Electronic spectrum of atomic chain with Fano-Anderson impurities - Skrypnyk, Yuriy V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
Electronic spectrum of one-dimensional system with a low concentration of weakly bound Fano-Anderson impurities is considered. It is assumed that the energy of the impurity resonance is located in a vicinity of the band center of the host system. It is demonstrated that with increasing the impurity concentration the dispersion of states with the low damping undergoes a transformation. This transformation passes in a threshold manner and results in the reproduction of some characteristic features inherent in the cross-type spectrum rearrangement. At that, the density of states at the energy of the impurity resonance manifests a steady growth.